Organizational Factors Associated with The Implementation of a Health Management Information System at Kenyatta National Hospital - Omambia, Salim M.; Karanja, Simon; Nyamongo, Daniel; Mutai, Joseph (Advances in Social Sciences Research Journal, 2023)
Healthcare organizations are increasingly spending and allocating huge budgets in embracing modern technology innovations and ways of dealing with healthcare related issues. While modern technology benefits cannot be disputed they however come at an expense and require a rigorous process before adopting the innovation. Studies done indicated Health care organizations find the process a rigmarole and opt for easier ways to incorporate or adopt the innovations, these usually results to a collapse or bottlenecks in the outputs of the innovations, in fact, majority of organizations have abandoned their ultra-modern system only to go back to their old manual system. The main objective of the study was to determine Organizational factors associated with implementation of a Health Management information Systems among healthcare workers at Kenyatta National Hospital. The research was conducted at KNH and adopted a cross-sectional study design. The target population of the study were 4,900 healthcare workers at KNH who were involved in implementing HMIS. The sample techniques used were mixed method sampling of stratified sampling, snowball sampling and convenience sampling. A sample total of 263 respondents was calculated for the quantitative study. The study utilized a questionnaire and a key informant interview schedule. Before processing the quantitative data, the data collected from the field was cleaned, coded, entered into a computer software and analyzed using SPSS version 21 while qualitative data was manually analyzed based on themes that were developed from responses (thematic analysis). Data presentation from the quantitative data was in form of quantitative statistics such as frequency distribution, percentages, tables, use of chi square for analysis, p values and odds ratios. Qualitative findings were presented in verbatim form. This study was submitted to KNH/UON Ethical Review Committee for ethical approval. Consenting was sought from individuals. Results indicated that majority of those interviewed were of the opinion that HMIS had improved services delivery by effecting efficiency especially in accident and emergency department, the wards and reception areas, generally there was improved efficiency in information handling in that, it had helped to identify patients in and through the system and there was reduction in costs. However, a few respondents were of the view that, HMIS had not improved efficiency to a larger extent since a lot of things were still done manually, no proper training and the system not fully implemented. Main challenges included, lack of technical assistance which led to loss of data which had never been recovered to date and scarce resources. In relation to the cadre of the hospital, the systems were quite complex, inadequate healthcare staff experience, scarcity of infrastructure and shortage of ICT technicians to assist in trouble shooting. There were very many refunds to patients by finance, resistance by users due to the perception that, it was a business-oriented system rather than goal oriented. Results show that the ratio of males to females was 1:1, 133(50.6%) and females 129(49.4%) thus gender balanced. A greater number of the respondents were aged between 26-35, 91 (34.6%), followed closely by the age bracket 36-45, 74(28.1%), the minority were aged 55 and above, 12(4.6%). In Kenyatta more than half of the respondent’s education level was college, 160(60.8%) with very few at secondary, 5(1.9%). population age, level of education and duration worked at KNH, (p value 0.008, 0.050 and 0.004). KNH might not be where they want or need to be as far as HMIS is concerned but they have made strides towards the right direction. Technologically, HIMS have already taken a vital role in the healthcare industry and are obliged to be organizational tools meant to create a better healthcare environment. It is essential for the KNH management to ensure that there is a systems thinking where each and every individual staff is not only motivated but also feels part and parcel of the HIMS process. KNH needs to devise a HIMS specifically for their clientele